Kidnapped in Yemen one woman's amazing escape from terrorist captivity - Quin, Mary (Mainstream, 2006)
When Mary Quin ripped an AK-47 from the hands of a wounded kidnapper and made her escape in the Yemeni desert, she knew her life could never be the same. An exotic vacation had turned into a nightmare. This is a first-hand account of the remarkable woman's unusual story of curiosity, survival and healing.